2015
DOI: 10.5603/ep.a2016.0019
|View full text |Cite
|
Sign up to set email alerts
|

Age may determine the effect of hypolipidemic agents on plasma adipokine levels in patients with elevated low-density lipoprotein cholesterol levels

Abstract: Introduction: Lipid-lowering agents affect adipose tissue function. No study has investigated the role of age in the effects of hypolipidaemic agents on plasma adipokines. Material and methods:The study was a retrospective analysis of data of 65 hypercholesterolaemic patients treated for 90 days with simvastatin, ezetimibe, or simvastatin/ezetimibe combination therapy. Circulating levels of leptin, adiponectin, visfatin, and tumour necrosis factor a (TNF-a), as well as high-sensitivity C-reactive protein (hsCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…Recent evidence has demonstrated that there are over 50 different adipokines secreted from adipose tissue [48][49][50][51]. The main processes regulated by adipokines may be divided into three groups: 1. lipids and glucose metabolism; 2. inflammatory processes; and 3. blood pressure and haemostasis.…”
Section: Hormonal Activity Of Adipose Tissuesmentioning
confidence: 99%
“…Recent evidence has demonstrated that there are over 50 different adipokines secreted from adipose tissue [48][49][50][51]. The main processes regulated by adipokines may be divided into three groups: 1. lipids and glucose metabolism; 2. inflammatory processes; and 3. blood pressure and haemostasis.…”
Section: Hormonal Activity Of Adipose Tissuesmentioning
confidence: 99%
“…Among many of them, leptin, adiponectin, resistin, visfatin, and others are mentioned [3]. Interestingly, previous studies on adipokines have focused mainly on aspects related to diabetes, obesity, metabolic syndrome, cardiomyopathy, anorexia nervosa, eating disorders, or tendency for atherogenesis [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…(25) Silva y su equipo evaluaron la precisión de las tres fórmulas para estimar c-LDL bajo en relación al medido directamente y su comparación con c-no-HDL y Apo B en pacientes con valores concordantes y discordantes de c-LDL, en el c-LDL <55 mg/dL se evidenció una tasa de discordancia de un 62,3 %, 50,9 % y 50% para Friedewald, Sampson y Martin-Hopkins respectivamente, siendo la fórmula de Friedewald la más inexacta pero a su vez las otras fórmulas también evidenciaron discordancias por lo que es mejor su medición directa. (31)…”
Section: Discussionunclassified